Molecular phylogeny of Calyptratae (Diptera: Brachycera): the evolution of 18S and 16S ribosomal rDNAs in higher dipterans and their use in phylogenetic inference - Nirmala, X; Hypsa, V; Zurovec, M (Insect molecular biology, 2001)
Sequences for nearly complete 18S rRNA and partial 16S rRNA genes were determined for sixteen species representing twelve calyptrate families. Two unique insertions are present in expansion regions of the 18S rDNA in nycteribiids. Alignments containing other dipteran rRNA genes provided good resolution at higher taxonomic level: monophyly of Calyptratae is well supported. While both 16S and 18S rDNA matrices produce unstable topologies within Calyptratae when analysed separately, their combination results in a tree with several robust and well supported nodes. Of three superfamilies recognized in recent classifications, the Hippoboscoidea is well supported by 16S rDNA and by combined matrices. The representatives of Muscoidea, Musca sp. and Antipoda sp., display a tendency to cluster within Oestroidea. The comparison of secondary structures of two variable regions indicates that Sarcophagidae are related to Calliphoridae rather than to Tachinidae.
Keywords: sekvence nukleotidů; Sequence Homology, Nucleic Acid; Nucleic Acid Conformation; Consensus Sequence; fylogeneze; RNA, Ribosomal, 18S; RNA, Ribosomal, 16S; Phylogeny; ribozomální DNA; molekulární sekvence - údaje; sekvenční homologie nukleových kyselin; molekulární evoluce; Evolution, Molecular; konformace nukleové kyseliny; Animals; konsenzuální sekvence; zvířata; RNA ribozomální 16S; Molecular Sequence Data; Base Sequence; DNA, Ribosomal; RNA ribozomální 18S; Diptera